ENVIRONMENTAL EDUCATION AND TOURISM: METHODOLOGIES FOR ENVIRONMENTAL EDUCATION APPLIED AS TOURIST-RECREATIONAL ACTIVITIES IN NATURAL SETTINGS - Bueno, Fernando Protti [UNESP] (Univ Estado Rio Grande Norte, 2016)
The purpose of this test is to identify and describe the structure of the methodologies for environmental education applied to different tourist and recreational activities in natural settings. There has been a growing demand in contemporary society by natural settings to perform activities inserted in the leisure (tourism, recreation and playfulness). This scope can be considered as a privileged means to promote practices and educational activities (environmental education). Thus, it is necessary to have specific forms, structures and organization methodologically to work with environmental education in tourism. In this exploratory and descriptive research, data collection was carried through bibliographical and documentary techniques. Thus, it was possible to identify as environmental education methodologies applied the tourist-recreational activities in natural settings, the methodology of Flow Learning (Joseph Cornell), the Environmental Interpretation (Sam Ham) and Experiential Education (Kurt Hahn). Mainly due to methodological structure of each of these, and consequently the possibility to achieve the principles of environmental education, it is considered that these methodologies can contribute to the planning and development of tourist and recreational practices aimed at raising awareness and the expansion of environmental awareness of tourists.
Keywords: ENVIRONMENTAL EDUCATION; TOURISM; FLOW LEARNING; ENVIRONMENTAL INTERPRETATION; EXPERIENTIAL EDUCATION